HASIL BELAJAR KETERAMPILAN MEMBACA BAHASA JERMAN DENGAN PENGGUNAAN MEDIA BIG BOOK PESERTA DIDIK KELAS X SMAN 1 SOOKO MOJOKERTO - MILADYAH FAUZAN, RIZKA (LATERNE, 2018)
This study examines the outcomes of learning the German language reading skills of students class X IPS-1 SMAN 1 Sooko Mojokerto. Learning of reading skills are not easy to learn if Students are not used to reading texts. Reading skills are important skills because it can affect proficiency in other language skills. Therefore, for learners interested, happy, and have a high motivation to read, used Big Book media that will facilitate learners in the learning process. The formulation of the problem in this research is "how is the learning outcomes of German reading skill with the use of Big Book media to the tenth grade students of SMAN 1 Sooko Mojokerto. The purpose of this research is to know and describe student learning outcomes with the use Big Book media for German reading skill to the tenth grade students of X IPS-1 SMAN 1 Sooko Mojokerto. This research is a descriptive qualitative research. Data in this study were obtained from research instrument. The instrument of this research is a meticulous test and non test in the form of questionnaire response and motivation of learners. The study was conducted during 4 meetings, application of the media performed at the second meeting until the fourth meeting. Results obtained data adjusted to the minimum competens criteria German and analyzed based on the theory of reading skills criteria (Buhlmann und Laveaus;1992). Based on the data descriptions of learning outcomes above, it can be concluded that, Big Book media can be used as an alternative teaching media that can facilitate students in learning German reading skills. It is seen from the data reading skill outcomes of the X IPS-1 students of SMAN 1 Sooko Mojokertpo showed a good learning progres at every meeting. Keywords : Learning Outcomes, Reading skill, Big Book